Quantification of the role of stabilized Criegee intermediates in the formation of aerosols in limonene ozonolysis - Y.W. Gong; Chen, Z. M. (Atmospheric Chemistry and Physics, 2021)
Stabilized Criegee intermediates (SCIs) have the potential to oxidize trace species and to produce secondary organic aerosols (SOA), making them important factors in tropospheric chemistry. This study quantitatively investigates the performance of SCIs in SOA formation at different relative humidity (RH), and the first- and second-generation oxidations of endo- and exo-cyclic double bonds ozonated in limonene ozonolysis are studied separately. Through regulating SCIs scavengers, the yields and rate constants of SCIs in reaction system were derived, and the amounts of SCIs were calculated. The amount of SOA decreased by more than 20% under low-humidity conditions (10–50% RH), compared to that under dry conditions due to the reactions of SCIs with water, while the inhibitory effect of water on SOA formation was not observed under high-humidity conditions (60–90% RH). When using excessive SCIs scavengers to exclude SCIs reactions, it was found that the effect of water on SOA formation with the presence of SCIs was different from that without the presence of SCIs, suggesting that SCIs reactions were relevant to the non-monotonic impact of water. The fractions of SCIs contribution to SOA were similar between dry and high-humidity conditions, where the SCIs reactions accounted for ~ 63% and ~ 73% in SOA formation in the first- and second-generation oxidation, however, marked differences in SOA formation mechanisms were observed. SOA formation showed a positive correlation with the amount of SCIs, and the SOA formation potential of SCIs under high-humidity conditions was more significant than that under dry and low-humidity conditions. It was estimated that 20–30% of SCIs could convert into SOA under high-humidity conditions, while this value decreased nearly by half under dry and low-humidity conditions. The typical contribution of limonene-derived SCIs to SOA formation is calculated to be (8.21 ± 0.15) × 10–2 μg m–3 h–1 in forest, (4.26 ± 0.46) × 10–2 μg m–3 h–1 in urban area, and (2.52 ± 0.28) × 10–1 μg m–3 h–1 in indoor area. Water is an uncertainty on the role of SCIs playing in SOA formation, and the contribution of SCIs to SOA formation needs consideration even under high RH in the atmosphere.